Molecular Detection of Norwalk-Like Caliciviruses in Sewage - Lodder, W. J. (American Society for Microbiology, 1999)
In this study, Norwalk-like virus (NLV) RNA was detected by reverse transcriptase PCR (RT-PCR) in sewage water concentrates. Sequence analysis of the RT-PCR products revealed identical sequences in stools of patients and related sewage samples. In 6 of 11 outbreak-unrelated follow-up samples, multiple NLV genotypes were present. Levels as high as 10(7) RNA-containing particles per liter were found. These data show that high loads of NLVs may be present in sewage and warrant further studies addressing the efficacy of NLV removal by sewage water treatment processes.